2018
DOI: 10.1007/s12663-018-1081-8
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Surgical, Electrosurgery and Diode Laser in the Management of Maxillofacial Nevus

Abstract: Purpose To compare the post-operative wound healing of patients treated for excision of the nevus/mole from maxillofacial region with surgical, electrosurgery and diode laser. Materials and Methods Forty-five clinically confirmed cases of benign nevus were included in the study and randomly divided into three groups according to the technique used for excision, i.e. Group A-surgical excision, Group B-diode laser and Group C-electrosurgery. Postoperative wound evaluation was done using Stony Brook scar evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Also, treatment of the face lesions with cryotherapy may be injurious due to hazard of immediate bullae formation and delayed pigmentary disturbances 26 . Reddy Bandral et al 1 compared the wound healing and scar formation in patients with facial nevus who were treated with electrosurgery, diode laser, and surgical excision and concluded that all the three techniques did not show any significant difference at the end of 3 months. The mentioned result, which was obtained with a lower‐frequency electrosurgery unit, should be considered as promising for radio‐wave surgery due to less lateral thermal damage potential of the latter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, treatment of the face lesions with cryotherapy may be injurious due to hazard of immediate bullae formation and delayed pigmentary disturbances 26 . Reddy Bandral et al 1 compared the wound healing and scar formation in patients with facial nevus who were treated with electrosurgery, diode laser, and surgical excision and concluded that all the three techniques did not show any significant difference at the end of 3 months. The mentioned result, which was obtained with a lower‐frequency electrosurgery unit, should be considered as promising for radio‐wave surgery due to less lateral thermal damage potential of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Humans’ demand to look attractive is increasing ever and it is quite usual for individuals to refer to a cosmetic surgery unit for the esthetic removal of nevi and various other benign lesions, including seborrheic keratosis, lentigo simplex, sebaceous hyperplasia, and syringoma 1,2 2,3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,6 Methods such as cautery, cryotherapy, and laser ablation provide less invasive alternatives, but can lead to hypopigmentation, hyperpigmentation, or recurrence. 4,6,14 Importantly, these options destroy tissue and prevent histologic evaluation. Despite the limitations, patients often elect to undergo one of these established techniques, sometimes presenting years later inquiring about scar minimization.…”
Section: Discussionmentioning
confidence: 99%
“…Os participantes foram acompanhados por 3 meses, os resultados mostraram que não houve diferenças significativas entre os 3 grupos a longo prazo, mas a avaliação a curto prazo mostrou que a técnica cirúrgica foi superior às outras duas técnicas 20 .…”
Section: Discussionunclassified